RESEARCH OF THE LIMING-UNHAIRING OF LEATHER PARCHMENT WITH THE PRESENCE OF THE NATURAL MINERAL ZEOLITE - KOLESNYK, Tetiana; ANDREYEVА, Olga; DAVYDIUK, Dmytro (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In many methods for the production of natural leather, the process of liming-unhairing is carried out using toxic sodium sulfide, poorly soluble calcium hydroxide, etc., this increases the degree of pollution of wastewater, complicates the work of treatment facilities. To improve the ecological situation, some works suggest replacing the widespread sulfide-lime liming-unhairing with a two-stage pure lime one or by using sodium hydroxide with kaolin together. In the development of this direction, this paper considers the possibility of using another natural mineral, zeolite, known for its high sorption capacity, during liming-unhairing. The paper investigates the hypothesis of a delayed action of calcium hydroxide on raw hides with the addition of zeolite. The hypothesis provides for the following mechanism: the absorbing complex of the zeolite sorbs calcium hydroxide ions, and after a while the reverse process gradually takes place - the zeolite gives Ca2+ and OH- ions back into the solution. This is confirmed by the results of studying the sorption-desorption kinetics of calcium hydroxide by zeolite depending on the concentration of lime and mineral. The influence of liming-unhairing conditions (lime-sulfide and sulfide-free using calcium hydroxide, calcium chloride in the presence of zeolite) on the formation of the structure and properties of the semi-finished leather product (pelt) and finished leather (parchment) is considered. The expediency of sulfide-free lime liming-unhairing in the presence of zeolite has been established, which makes it possible to obtain a strong, filled leather with a reduced consumption (or even complete exclusion) of environmentally harmful chemical reagents.
Keywords: leather parchment; liming-unhairing; zeolite